2007
DOI: 10.1007/s11109-007-9033-x
|View full text |Cite
|
Sign up to set email alerts
|

Some Children See Him...: Political Participation and the Black Christ

Abstract: This paper explores the role that membership in a politicized church and believing in a black Christ have on the political mobilization and participation of African Americans. Using data from the 1993-94 National Black Politics Study (NBPS), the authors conclude that imagining a black Christ is a radicalizing force on political participation. Hearing politicizing messages in a place of worship and believing that Christ is black appears to shift African Americans from relatively conservative or traditional form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Religious institutions also support the positive material, social, moral, educational, physical, and behavioral outcomes of Black community members by providing outreach and in-reach programs and initiatives including social events (e.g., concerts, dances), educational programs, leadership opportunities, health initiatives, financial supports, and family support programs (Beyerlein and Chaves 2003;Brown and Brown 2003;Caldwell et al 1995;Jeynes 2002;Johnson and Carter-Edwards 2015;Morris 1996;McRoberts 2003;Rowland and Isaac-Savage 2014;Sullivan 2008). Further, these institutions support positive development by noticing and building on the talents, intellectual resources, and skills of individuals within the community and by cultivating in people a sense of responsibility to use these assets for both personal development and family and community enrichment (Gilkes 2001;Grayman-Simpson and Mattis 2013;Mamiya 2006;Reese et al 2007).…”
Section: Urban Contexts Religious Institutions and Positive Developmentioning
confidence: 99%
“…Religious institutions also support the positive material, social, moral, educational, physical, and behavioral outcomes of Black community members by providing outreach and in-reach programs and initiatives including social events (e.g., concerts, dances), educational programs, leadership opportunities, health initiatives, financial supports, and family support programs (Beyerlein and Chaves 2003;Brown and Brown 2003;Caldwell et al 1995;Jeynes 2002;Johnson and Carter-Edwards 2015;Morris 1996;McRoberts 2003;Rowland and Isaac-Savage 2014;Sullivan 2008). Further, these institutions support positive development by noticing and building on the talents, intellectual resources, and skills of individuals within the community and by cultivating in people a sense of responsibility to use these assets for both personal development and family and community enrichment (Gilkes 2001;Grayman-Simpson and Mattis 2013;Mamiya 2006;Reese et al 2007).…”
Section: Urban Contexts Religious Institutions and Positive Developmentioning
confidence: 99%
“…Reese et al (2007) found that hearing politicizing messages or a theology of black liberation serves as a radicalizing force for black churchgoers. Mamiya (2006) reports that of the black Protestant denominations, ministers of Christian Methodist Episcopal churches, followed by African Methodist Episcopal (A.M.E.) and African Methodist Episcopal Zion churches, are most likely to preach sermons on social justice or social action and make references to the racial situation in society.…”
Section: Black Church Activismmentioning
confidence: 99%
“…It has been linked to the rise of racial conservatism among Blacks and the rise of neoliberalism among Black elites (Harris-Lacewell, 2007a, 2007b; Spence, 2015). Black liberation theology argues that there is a parallel between the experiences of Blacks in America and the persecution biblical figures, and has been linked calls for a radical change, such as Black nationalism and Black feminism (Calhoun-Brown, 1999; Cone & Wilmore, 1993; Reese, Brown, & Ivers, 2007; Reese & Brown, 1995).…”
Section: Introductionmentioning
confidence: 99%